2023
DOI: 10.1039/d3dt02113k
|View full text |Cite
|
Sign up to set email alerts
|

Variation in pnictogen–oxygen bonding unlocks greatly enhanced Brønsted basicity for the monomeric stibine oxide

John S. Wenger,
Addis Getahun,
Timothy C. Johnstone

Abstract: We recently reported the first example of a monomeric stibine oxide. Herein, we assess the Brønsted basicity of a series of monomeric pnictine oxides (Dipp3PnO; Pn = P, As, and Sb).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The Dipp substituents are sufficiently sterically demanding to kinetically stabilize a monomeric, bench-stable species that can engage in H-bonding, Bro̷nsted base chemistry, coordination chemistry, and O atom transfer. The Bro̷nsted basicity of Dipp 3 SbO is dramatically enhanced over that of the lighter congeners, and our molecular orbital calculations suggested that Dipp 3 SbO enjoys a similarly privileged Lewis acidity . Access to the Lewis acidic Sb atom is, however, largely precluded by the steric shielding of the Dipp substituents.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…The Dipp substituents are sufficiently sterically demanding to kinetically stabilize a monomeric, bench-stable species that can engage in H-bonding, Bro̷nsted base chemistry, coordination chemistry, and O atom transfer. The Bro̷nsted basicity of Dipp 3 SbO is dramatically enhanced over that of the lighter congeners, and our molecular orbital calculations suggested that Dipp 3 SbO enjoys a similarly privileged Lewis acidity . Access to the Lewis acidic Sb atom is, however, largely precluded by the steric shielding of the Dipp substituents.…”
Section: Introductionmentioning
confidence: 72%
“…Phosphine oxides and arsine oxides are commonly used as Lewis bases, and in our earlier work we studied the interaction between Dipp 3 SbO and transition-metal centers . This coordination chemistry, in combination with the dramatically enhanced Bro̷nsted basicity of Dipp 3 SbO relative to its lighter congeners, led us to anticipate that the stibine oxide would readily form stable Lewis adducts with a wide variety of main-group Lewis acids. As an initial test of this capability, we investigated its reaction with PbMe 3 Cl, which features a sterically unencumbered Pb atom capable of expanding its coordination sphere and a low-lying Pb–Cl σ* orbital into which it can accept electron donation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the first to be prepared was the antimony analog of arsanilic acid, which was described as "para-aminophenylstibinic acid" (although it would now be called para-aminophenylstibonic acid) and given the moniker stibamine. [139] Although the compound was initially described as a monomeric stibonic acid, it is now known that, like arylstibine oxides, [101][102][103][140][141][142] arylstibonic acids can self-associate into higher-nuclearity structures. [143][144][145][146] In the absence of oligomerization, they may also remain monomeric but expand their coordination sphere, possibly with ligand exchange occurring.…”
Section: Outlook: Pentavalent Antimonialsmentioning
confidence: 99%
“…The relative Brønsted basicity of Dipp 3 PnO (Pn = P, As, Sb) was probed. 96 Based on the theoretical analyses described above, we hypothesized that the Lewis basicity at the O atom would increase from Dipp 3 PO < Dipp 3 AsO < Dipp 3 SbO. Treatment of Dipp 3 PnO with triflic acid afforded the corresponding [Dipp 3 PnOH][CF 3 SO 3 ] salt in all cases.…”
Section: Monomeric Stibine Chalcogenidesmentioning
confidence: 99%